2005
DOI: 10.1002/bit.20507
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of human serum albumin production in methylotrophic yeast Pichia pastoris by repeated fed‐batch fermentation

Abstract: An optimization method for repeated fed-batch fermentation was established with the aim of improving the recombinant human serum albumin (rHSA) production in Pichia pastoris. A simulation model for fed-batch fermentation was formulated and the optimal methanol-feeding policy calculated by dynamic programming method using five different methanol-feeding periods. The necessary state variables were collected from the calculated results and used for further optimization of repeated fed-batch fermentation. The opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 29 publications
3
37
0
Order By: Relevance
“…When using this expression system, q P increases asymptotically to a maximum value with increasing m ). An analogous behavior has been also reported for the AOX1 promoter for P. pastoris cells growing on methanol (Ohya et al, 2005). Hence the ratio of q P to m, which corresponds to the yield of product per biomass (Y PX ) decreases with increasing m, so that low product titers are achieved at higher growth rates.…”
Section: Introductionsupporting
confidence: 73%
“…When using this expression system, q P increases asymptotically to a maximum value with increasing m ). An analogous behavior has been also reported for the AOX1 promoter for P. pastoris cells growing on methanol (Ohya et al, 2005). Hence the ratio of q P to m, which corresponds to the yield of product per biomass (Y PX ) decreases with increasing m, so that low product titers are achieved at higher growth rates.…”
Section: Introductionsupporting
confidence: 73%
“…Process optimization efforts included optimization of expression conditions such as temperature, dissolved oxygen, cell density, osmotic stress, medium composition, pH, and the methanol feed rate (Charoenrat et al, 2005;Cunha et al, 2004;Damasceno et al, 2004Damasceno et al, , 2007Jungo et al, 2007c;Khatri and Hoffmann, 2006;Ramon et al, 2007;Shi et al, 2003;Trentmann et al, 2004). Potgieter et al (2009) reported that process variables such as pH, temperature, and dissolved oxygen within the ranges evaluated had only a marginal impact on antibody expression in glycoengineered yeast but consistent with the findings of several other investigators have found that the methanol feed rate had a substantial impact on specific productivity (Cunha et al, 2004;Hensing et al, 1995;Ohya et al, 2005;Potgieter et al, 2009;Sinha et al, 2003).…”
Section: Introductionsupporting
confidence: 71%
“…Other investigators worked on establishing a relationship between the methanol feed rate and the protein production rate to enable modeling and optimization through algorithms such as Pontryagin's Maximum Principle (Zhang et al, 2005), Green's Theorem or Dynamic Programming (d'Anjou and Daugulis, 2001;Ohya et al, 2005;Zhang et al, 2000a,b). In these cases the optimization problem was constrained by the maximum biomass concentration, the maximum reactor volume and a minimum induction time Zhang et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Examples can be found in which it has been approximated by a several step linear function (Ohya et al, 2005). The parameters of this function are experimentally determined in continuous cultures growing at different specific growth rates.…”
Section: A·μ π (17)mentioning
confidence: 99%
“…Kinetic expressions of protein productivity as a function of specific growth rate (P) have also been broadly used (Cunha et al, 2004;Zhang et al, 2004;Jungo et al, 2007). However, the exact function S = f(P) of this dependence is still subject to discussion (Maurer et al, 2006;Dietzsch et al, 2010) and may be highly nonlinear, monotonously increasing, decreasing, or even nonmonotonous (Curvers et al, 2002;Sinha et al, 2003;Ohya et al, 2005;Potgieter et al, 2010). It would seem that specific growth rate is only an indirect estimator for protein productivity that can only be adjusted locally to trustworthy functions.…”
Section: Introductionmentioning
confidence: 99%